1988
DOI: 10.1128/jcm.26.11.2257-2261.1988
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-linked immunosorbent assay to evaluate the immunogenicity of a polyvalent Klebsiella capsular polysaccharide vaccine in humans

Abstract: A highly sensitive enzyme-linked immunosorbent assay was developed for Klebsiella capsular polysaccharide (CPS) and used to evaluate the immunoglobulin G (IgG) antibody response to a 24-valent CPS vaccine in seven adult volunteers. The median rise in titer to all vaccine antigens in samples from the volunteers was significant (twofold or greater). Significant IgG responses to 11 immunologically related serotypes not included in the vaccine were also noted. The mean cross-reacting IgG titer of 127.2 was only sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Since most fatal gram negative bacillary infections are caused by Escherichia coli, Pseudotnonas aeruginosa and Klebsiella species, it would be useful to have some form of immunoprophylaxis specific to these organisms. To this end, investigators have recently constructed protein conjugate vaccines to the O‐polysaccharides of E. coli and P. aeruginosa , as well as a multivalent Klebsiella capsular polysaccharide vaccine 225 227 . Each of these preparations is immunogenic in humans, and may ultimately be useful both for active immunization of high risk individuals as well as for preparation of hyperimmune gammaglobulin from immunized healthy individuals.…”
Section: Future Directions‐new Approaches To Vaccinationmentioning
confidence: 99%
“…Since most fatal gram negative bacillary infections are caused by Escherichia coli, Pseudotnonas aeruginosa and Klebsiella species, it would be useful to have some form of immunoprophylaxis specific to these organisms. To this end, investigators have recently constructed protein conjugate vaccines to the O‐polysaccharides of E. coli and P. aeruginosa , as well as a multivalent Klebsiella capsular polysaccharide vaccine 225 227 . Each of these preparations is immunogenic in humans, and may ultimately be useful both for active immunization of high risk individuals as well as for preparation of hyperimmune gammaglobulin from immunized healthy individuals.…”
Section: Future Directions‐new Approaches To Vaccinationmentioning
confidence: 99%
“…The obstacle for the successful preparation of such K-antigen-based immunologic tool is the fact that there are more than 70 K antigens expressed on clinical isolates, most of them present in 1%–2% of clinical strains [ 12 , 13 ]. Indeed, Cryz and coworkers developed a K-antigen-based vaccine containing purified polysaccharides of 24 capsular serotypes [ 14 , 15 ]. A hyperimmune intravenous immunoglobulin (Ig) preparation made from the postvaccination plasma of volunteers immunized simultaneously with the Klebsiella K antigen and Pseudomonas vaccines has undergone a randomized clinical trial with intensive care patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that pulmonary and bloodstream infections caused by klebsiellae result in high rates of mortality despite the use of potent antimicrobial agents (3,27) has acted as a stimulus to researchers to develop immunologic strategies for their prevention and treatment. Since it has been shown that the Klebsiella capsule (K antigen) plays an important role in pathogenicity (12,41), Cryz and coworkers developed a capsular antigen-based vaccine containing the purified polysaccharides of 24 capsular serotypes (7,15). A hyperimmune intravenous immunoglobulin (Ig) preparation made from the postvaccination plasma of volunteers immunized simultaneously with the Klebsiella capsular antigen and Pseudomonas vaccines has recently undergone a randomized clinical trial with intensive-care patients (9).…”
mentioning
confidence: 99%